Pain in the cancer patient: different pain characteristics CHANGE pharmacological treatment requirements. (September 2014) - Müller-Schwefe, Gerhard; Ahlbeck, Karsten; Aldington, Dominic; Alon, Eli; Coaccioli, Stefano; Coluzzi, Flaminia; Huygen, Frank; Jaksch, Wolfgang; Kalso, Eija; Kocot-Kępska, Magdalena; Kress, Hans-Georg; Mangas, Ana Cristina; et al.
Abstract Twenty years ago, the main barriers to successful cancer pain management were poor assessment by physicians, and patients' reluctance to report pain and take opioids. Those barriers are almost exactly the same today. Cancer pain remains under-treated; in Europe, almost three-quarters of cancer patients experience pain, and almost a quarter of those with moderate to severe pain do not receive any analgesic medication. Yet it has been suggested that pain management could be improved simply by ensuring that every consultation includes the patient's rating of pain, that the physician pays attention to this rating, and a plan is agreed to increase analgesia when it is inadequate. After outlining current concepts of carcinogenesis in some detail, this paper describes different methods of classifying and diagnosing cancer pain and the extent of current under-treatment. Key points are made regarding cancer pain management. Firstly, the pain may be caused by multiple different mechanisms and therapy should reflect those underlying mechanisms – rather than being simply based on pain intensity as recommended by the WHO three-step ladder. Secondly, a multidisciplinary approach is required which combines both pharmacological and non-pharmacological treatment, such as psychotherapy, exercise therapy and electrostimulation. The choice of analgesic agent and its route of administration are considered, along with various interventional procedures and the requirements of palliative care. Special attention is paid to the treatment of breakthrough pain (particularly with fast-acting fentanyl formulations, which have pharmacokinetic profiles that closely match those of breakthrough pain episodes) and chemotherapy-induced neuropathic pain, which affects around one third of patients who receive chemotherapy. Finally, the point is made that medical education should place a greater emphasis on pain therapy, both at undergraduate and postgraduate level.